2019
DOI: 10.3899/jrheum.181084
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an OMERACT MRI Whole-Body Score for Inflammation in Peripheral Joints and Entheses in Inflammatory Arthritis (MRI-WIPE)

Abstract: Objective.To develop a whole-body magnetic resonance imaging (MRI) scoring system for peripheral arthritis and enthesitis.Methods.After consensus on definitions/locations of MRI pathologies, 4 multireader exercises were performed. Eighty-three joints were scored 0–3 separately for synovitis and osteitis, and 33 entheses 0–3 separately for soft tissue inflammation and osteitis.Results.In the last exercise, reliability was moderate-good for musculoskeletal radiologists and rheumatologists with previously demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 15 publications
0
25
0
1
Order By: Relevance
“…WBMRI may, in the future clinical practice aid in diagnosis of early forms of SpA, enabling evaluation of both axial and peripheral entheses and joints. (40)(41)(42) Readability and reproducibility of WBMRI were high in spine and SI joints, but lower in the peripheral joints in earlier studies (43). However, a more recent study has found good reliability in peripheral entheses too (41).…”
Section: Utility Of Mri In the Diagnosis Of Enthesitis In Spamentioning
confidence: 89%
See 4 more Smart Citations
“…WBMRI may, in the future clinical practice aid in diagnosis of early forms of SpA, enabling evaluation of both axial and peripheral entheses and joints. (40)(41)(42) Readability and reproducibility of WBMRI were high in spine and SI joints, but lower in the peripheral joints in earlier studies (43). However, a more recent study has found good reliability in peripheral entheses too (41).…”
Section: Utility Of Mri In the Diagnosis Of Enthesitis In Spamentioning
confidence: 89%
“…For MRI assessment of enthesitis in clinical trials, it is recommended to apply validated assessment methods, such as the OMERACT MRI scoring systems (27,41). More studies are needed to validate and optimize the existing MRI outcome measures.…”
Section: How Have Clinical Trials Applied Mri For Assessing Enthesitis?mentioning
confidence: 99%
See 3 more Smart Citations